Fertility after timed artific[i]al insemination in response to a Controlled Internal Drug Release (CIDR) insert in lactating dairy cows - Martel, Cynthia Ann (Kansas State University, 2008)
Lactating dairy cows from 2 Kansas farms were used to determine the effectiveness of exogenous progesterone in the form of an intravaginal insert (controlled internal drug release; CIDR) in conjunction with an ovulation-synchronization protocol. Cows were enrolled in a Presynch + Ovsynch protocol after parturition, where they received 2 injections of PGF[subscript]2[alpha], 14 d apart (Presynch) beginning between 30 and 36 DIM. Cows (n = 155) detected in estrus after the second PGF[subscript]2[alpha] injection of Presynch were inseminated (early AI). Remaining cows were assigned randomly to be treated with the Cosynch-72 protocol (GnRH 12 d after last Presynch PGF[subscript]2[alpha] injection, PGF[subscript]2[alpha] 7 d after GnRH, and timed AI + GnRH injection 72 h later) and served as controls (n = 159), or to be treated with the Cosynch-72 protocol and receive a progesterone insert (Ovsynch + CIDR; n = 175) for 7 d between GnRH and PGF[subscript]2[alpha]. Blood was collected at d −22 and −10 (relative to TAI at d 0) to determine cycling status based on progesterone concentrations and again at d 11 post AI to determine luteal competency. Treated cows were assigned body condition scores (BCS) on d −22 and −10. Pregnancy status was confirmed by palpation of the uterus per rectum and its contents on d 38 post-timed AI and verified again 4 wk later. Treatment with the progesterone insert increased timed AI pregnancies per AI in Cosynch- 72 + CIDR-treated cows when compared with controls (38 vs. 24%), but did not differ from early AI cows (38%). Pregnancy loss was numerically less in progesterone-treated cows than in controls (4.4 vs. 11.8%). Our study shows that increased pregnancies per AI can be achieved by the use of a progesterone insert in a reduced population of cows not yet inseminated, but treated with a progesterone insert.
Keywords: Lactating Dairy cows; CIDR; Progesterone insert; Ovulation synchronization; Ovsynch; Presynch-Ovsynch; Agriculture, General (0473)